Assessment of Growth in Pediatric Syrian Refugee Populations in Jordan - Amanda Vakos (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Background Externally displaced pediatric Syrian refugees are at risk of adverse developmental health outcomes in the setting of food insecurity. To evaluate the impact of displacement on nutritional status of Syrian children, this study describes the prevalence of malnutrition of Syrian children residing in Jordan. Methods A retrospective cross-sectional analysis of data from patient records < 18 years of age from the Syrian American Medical Society's (SAMS) January 2019 mission trip to Jordan was performed. Prevalence of stunting, severe wasting, wasting, overweight, and underweight were calculated using the World Health Organization (WHO) definitions. Results Overall, 392 Syrian children were included. In the 0 to 59 months group (n = 191), prevalence of stunting was 13.9% (n = 165), severe wasting 4.2% (n = 165), wasting 6% (n = 165), overweight 16.4% (n = 165), and underweight 5.3% (n = 190). In the > 59 months group (n = 201), prevalence of stunting was 7.2% (n = 194), severe wasting 3.6% (n = 194), wasting 5.2% (n = 194), overweight 6.7% (n = 194), and underweight 4.6% (n = 153). Age group was significantly associated with stunting (odds ratio [OR]  = 2.08,9 5% CI 1.03 to 4.19) and overweight (OR = 2.72; 95% CI 1.36 to 5.47) with increased odds of each in the 0–59 months group. Conclusion The findings suggest evidence of higher prevalence of malnutrition in Syrian children compared with prior assessments and greater impact on the younger cohort. In 0 to 59 months' old Syrian children, stunting and wasting were of medium severity and overweight was of high severity. This may reflect food insecurity in the setting of ongoing conflict, strain on resources, and evolving refugee policies, acknowledging study limitations. Syrian refugee children living in Jordan experience wasting and stunting. Comprehensive assessment of current nutritional status of Syrian children is needed. Access to adequate and nutritious food is paramount.